PENGARUH PEMBERIAN PUPUK KCl TERHADAP N, P, K TANAH DAN SERAPAN TANAMAN PADA INCEPTISOL UNTUK TANAMAN JAGUNG DI SITU HILIR, CIBUNGBULANG, BOGOR - F Fi’liyah; N Nurjaya; S Syekhfani (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
KCl is an inorganic fertilizer needed by maize plant for photosynthesis processes, vegetative crop growth, improving yield in the forms of flower and fruit. The purpose in this study was to understand the effect of KCl on soil N, P, and K, and nutrient uptake by maize plant.Â Treatments tested in this study were P0 = control; P1 = KCl 100 (from Canada); P2 = KCl 25 (froml Rusia); P3 = KCl 50 (from Rusia); P4 = KCl 75 (from Rusia); P5 = KCl 100 (from Rusia); P6 = KCl 125 (from Rusia); P7 = KCl 150 (from Rusia). Each treatment was supplied with Urea 350 kg ha-1 and SP-36 250 kg ha-1 as basal fertilizers. Results of this study showed that that application of different doses of KCl fertilizer significantly affected maize yield as well as N, P, and K uptake by maize. The highest dry seed yield of 6.97 t ha-1 was observed for the P5 treatment. The highest N uptake of 34.68 kg ha-1 was observed for the P1 treatment, the highest P uptake of 8.58 kg ha-1 was on the P7 treatment, and the highest K uptake of 23.38 kg ha-1 was on the P7 treatment. Application of KCl fertilizer resulted in residual N, K and P that ranging from 0.0769-0.0821%, 64.24-104.44 ppm, and 0.261-0.326%, respectively